The U.S. commitment to global health : recommendations for the public and private sectors (Online access: NCBI NCBI Bookshelf., 2009)
The U.S. Commitment to Global Health examines ways in which the United States could contribute to advances in global health, including the following four areas of action: Generate and share knowledge to address problems endemic to poor countries, Invest in people, institutions, and capacity building in resource-poor settings, Increase both quantity and quality of U.S. financial commitments to global health, Be a respectful partner and leader.